2011
DOI: 10.1002/pon.2053
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sense of coherence to stressful events, coping strategies, health status, and quality of life in women with breast cancer

Abstract: Sense of coherence significantly predicts distress, number and type of coping strategies such as direct action and relaxation, health status, and QoL in women with breast cancer. Our data suggest that the SOC scale may be a useful screening tool to identify individuals particularly vulnerable to distress and unable to cope adequately. Assessing SOC strength may assist health care providers to provide individualized patient interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
92
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 40 publications
15
92
0
3
Order By: Relevance
“…There are other studies 38 that have concluded that SOC theory can be used to understand how people reflect on how they cope with problems in their everyday lives. Sarenmalm et al (2013) suggest that SOC could be useful as a tool for identifying individuals in need of support to cope with breast cancer 39 . Strengthening existing resources and identification of new resources could help young survivors adapt to a changed life following childhood cancer.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…There are other studies 38 that have concluded that SOC theory can be used to understand how people reflect on how they cope with problems in their everyday lives. Sarenmalm et al (2013) suggest that SOC could be useful as a tool for identifying individuals in need of support to cope with breast cancer 39 . Strengthening existing resources and identification of new resources could help young survivors adapt to a changed life following childhood cancer.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…Many studies have analyzed the coping strategies that patients adopt when they face this disruptive experience (recently, Sarenmalm, Browall, Persson, Fall-Dickson, & Gaston-Johansson, 2013;Silva, Crespo, & Canavarro, 2012) mainly with a focus on individualistic coping strategies such as positivity, fighting spirit, or other stable personality traits, such as "sense of coherence" (Antonovsky, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…th International Conference on Healthcare, Environment, Food and Biological Sciences (HEFBS-17) Istanbul (Turkey) Sept. [8][9][10]2017 mourning is prolonged. Method of cognitive behavioral therapy helps confront the emotional drain and grief acceptance, increasing the spiritual well-being and emotional intelligence of the elderly bereavement.…”
Section: Introductionmentioning
confidence: 99%